STUDY AND IMPROVEMENT OF PERFORMANCE OF NoSQL DATABASES: MongoDB, HBase and OrientDB. - Noel Bila; Bopatriciat Boluma Mangata; Eugène MBUYI MUKENDI; Parfum BUKANGA CHRISTIAN (IJISCS (International Journal of Information System and Computer Science), 2022)
This dissertation adds to the various research works in the field of NoSQL "Not only SQL" databases. These new models propose a new way of organizing and storing data designed mainly to remedy the constraints imposed by the ACID properties on relational models. Our objective was to develop a comparative performance study, between three NoSQL solutions widely used in the market, namely: MongoDB, HBase and OrientDB, to propose to decision makers, elements of information for possible choices of the best appropriate solution for their companies. The Benchmark used to decide between these solutions is the Yahoo Cloud Serving Benchmark.